An assessment of the rescue action of resveratrol in parkin loss of function-induced oxidative stress in Drosophila melanogaster. - Adedara, A.O.; Babalola, A.D.; Stephano, F.; Awogbindin, I.O.; Olopade, J.O.; Rocha, J.B.T.; Whitworth, A.J.; Abolaji, A.O. (Scientific reports, 2022)
Loss-of-function mutations in parkin is associated with onset of juvenile Parkinson's disease (PD). Resveratrol is a polyphenolic stilbene with neuroprotective activity. Here, we evaluated the rescue action of resveratrol in parkin mutant D. melanogaster. The control flies (w1118) received diet-containing 2% ethanol (vehicle), while the PD flies received diets-containing resveratrol (15, 30 and 60 mg/kg diet) for 21 days to assess survival rate. Consequently, similar treatments were carried out for 10 days to evaluate locomotor activity, oxidative stress and antioxidant markers. We also determined mRNA levels of Superoxide dismutase 1 (Sod1, an antioxidant gene) and ple, which encodes tyrosine hydroxylase, the rate-limiting step in dopamine synthesis. Our data showed that resveratrol improved survival rate and climbing activity of PD flies compared to untreated PD flies. Additionally, resveratrol protected against decreased activities of acetylcholinesterase and catalase and levels of non-protein thiols and total thiols displayed by PD flies. Moreover, resveratrol mitigated against parkin mutant-induced accumulations of hydrogen peroxide, nitric oxide and malondialdehyde. Resveratrol attenuated downregulation of ple and Sod1 and reduction in mitochondrial fluorescence intensity displayed by PD flies. Overall, resveratrol alleviated oxidative stress and locomotor deficit associated with parkin loss-of-function mutation and therefore might be useful for the management of PD.